PEMANFAATAN DAUN JATI DAN DAUN MANGGA SEBAGAI SUMBER PEWARNA ALAMI UNTUK KAIN PADA PENGRAJIN TENUN LOMBOK BERBASIS GREEN TEKNOLOGI - Kurniawidi, Dian W.; Ardianto, Teguh; Alaa', Siti; Alhadi, Kasnawi; Dewi, Diah L.; S., RR. Delima; Rahayu, Susi (Jurnal Abdi Insani, 2024)
The Mandalika Central Lombok Special Economic Zone (SEZ) is one of the world-class national priority tourist destinations. However, until now there has been no branding of the village's superior woven products that can contribute significantly to the Mandalika SEZ. So it is important to carry out this service activity, to give birth to entrepreneurial pioneer weaving craftsmen towards "LOMBOK WEANING, LOCAL GOING GLOBAL". To achieve this goal, the craftsmen group experienced several problems (1) limited insight into the importance of developing weaving for the tourism sector towards international tourism and (2) the dyeing process was still using conventional methods which took a long time and was impractical. This problem arose due to a lack of human resources owned by the village, even though the natural resource potential it has really supports the songket weaving industrial center. Therefore, the role of academics is really needed to innovate to provide solutions to problems based on green technology. The solutions to the problems that will be offered are (1) activities to open people's insight into the importance of the tourism sector (2) dissemination of green synthesis technology using a modified steam extraction method to produce natural dye powder accompanied by students of the material characterization method course (3 credits). So that both solutions can be delivered appropriately, a systematic flow of activities needs to be carried out consisting of (a) socialization, training, (c) mentoring, and (d) monitoring and evaluation. A series of activities have been carried out, it is hoped that the craftsmen's skills will increase so that they are able to independently produce coloring powder from various existing local natural resources and be able to compete internationally. In addition, different types of leaves will produce different color pigments. Differences in dyeing processes and techniques will produce cotton threads with different qualities. In general, natural dyes always produce soft colors.